Representa????es sociais e comunica????o organizacional: o espa??o conceito como inst??ncia discursiva - Braga, Tatyanna Castro da Silva (2013)
This thesis deals with the study of social representations theory within organizational communication, specifically in institutional discourse as a way to position a brand in the market by exploiting resources sensory awakening the senses of consumers, in the ambience of the space physical, to bring them closer to the brand. Therefore, it was used as a scientific methodology content analysis of textual elements present in the company's website Natura and semiotic analysis of the ambient Space Concept Natura to achieve the objective of identifying social representations adopted by the organization in its institutional discourse and highlight how she anchored and aimed such elements at promoting a sensory experience of their consumers with the brand, in order to reassert its institutional discourse. As a result of comparison between the two studies, content analysis and semiotics, we can observe the convergence and consistency of the proposed speech by the organization, supporting the institutional discourse on this site and enacting it in physical space of the brand.